Blood mRNA Expression Profiles of Autophagy, Apoptosis, and Hypoxia Markers on Blood Cardioplegia and Custodiol Cardioplegia Groups - Elcik,Deniz (2021)
Abstract Introduction: Blood cardioplegia (BC) and Custodiol cardioplegia (CC) have been used for a long time in open heart surgery and are highly effective solutions. The most controversial issue among these two is whether there is any difference between them regarding myocardial damage after ischemia surgery. In this study, autophagy, apoptosis, and hypoxia markers were investigated and that way we evaluated the differences between BC and CC patients. Methods: A total of 30 patients were included in this study, using two different cardioplegic solutions. Three different whole blood samples of the patients were taken from a central vein (preoperatively, immediately postoperatively, and one day after surgery). Total ribonucleic acid was extracted from these samples. Quantitative real-time polymerase chain reaction was performed, and changes in gene expression were determined by the 2-∆∆Ct method of relative quantification. Results: In the CC group, Beclin gene expression level was found to be higher and this difference was statistically significant (P=0.0024). Similarly, cysteine-aspartic acid protease (caspase) 9 and hypoxia-inducible factor 1α messenger ribonucleic acid (mRNA) gene expression level increased and were significantly different in the CC group. In the BC group, Beclin and microtubule-associated protein light chain 3 expressions were higher in the samples taken one day after surgery. Caspases 3 and 8 gene expressions were significantly different in the BC group. Conclusion: As a result of the analysis performed between the two cardioplegia groups, it has been shown that CC harms the myocardium more than BC at the level of mRNA expression of related markers.